2017
DOI: 10.1016/j.devcel.2017.07.023
|View full text |Cite|
|
Sign up to set email alerts
|

HBL1 Is a Human Long Noncoding RNA that Modulates Cardiomyocyte Development from Pluripotent Stem Cells by Counteracting MIR1

Abstract: Summary Cardiogenesis processes in human and animals have differential dynamics, suggesting the existence of species–specific regulators during heart development. However, it remains a challenge to discover the human-specific cardiac regulatory genes, given that most coding-genes are conserved. Here, we report the identification of a human-specific long noncoding RNA, Heart Brake LncRNA 1 (HBL1), which regulates cardiomyocyte development from human induced pluripotent stem cells (hiPSCs). Overexpression of HBL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 66 publications
0
48
0
Order By: Relevance
“…In further analyzing genes differentially expressed in our HERV-H knockout lines, we discovered that the human-specific long-coding RNA (lncRNA), Heart Brake ( HBL1 ), which has been reported recently to suppress cardiomyocyte differentiation 45 , was also significantly reduced in the HERV-H1-KO hESCs ( Supplementary Fig. 9g ).…”
Section: Resultsmentioning
confidence: 99%
“…In further analyzing genes differentially expressed in our HERV-H knockout lines, we discovered that the human-specific long-coding RNA (lncRNA), Heart Brake ( HBL1 ), which has been reported recently to suppress cardiomyocyte differentiation 45 , was also significantly reduced in the HERV-H1-KO hESCs ( Supplementary Fig. 9g ).…”
Section: Resultsmentioning
confidence: 99%
“…As one of the most commonly used cell models for lncRNA studies, PSCs have been extensively profiled for RNA expression, epigenetic modifications, and RNA-protein interactions ( Guttman et al., 2009 , Guttman et al., 2011 , Kelley and Rinn, 2012 ). Functional studies have indicated that lncRNAs are involved in the self-renewal of PSCs through regulating key pluripotency factors ( Kaneko et al., 2014 , Perry and Ulitsky, 2016 , Sheik Mohamed et al., 2010 ), mediating chromatin modifications ( da Rocha et al., 2014 , Jain et al., 2016 , Lin et al., 2014 ), or sponging/counteracting microRNAs ( Liu et al., 2017 , Wang et al., 2013 ). However, the lists of potentially functional lncRNAs in ESCs that have been reported by different studies overlap poorly ( Guttman et al., 2011 , Kaneko et al., 2014 ), which suggests that the functions of lncRNAs in PSCs are still not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Heart Brake LncRNA 1 is a human-specific lncRNA related to cardiomyocyte differentiation. HBL1 over-expression suppresses cardiomyocyte differentiation by down-regulating GATA4, CTNT, NKX2.5, TBX5, TBX20 and α-MHC expression while its silencing has opposite effects (Liu et al, 2017). Mechanistically, HBL1 can interact and sponge miR-1, a key cardiomyocyte differentiation promoter, to impair cardiomyocyte differentiation (Lu T.Y.…”
Section: Lncrna In Cardiovascular Developmentmentioning
confidence: 99%
“…Mechanistically, HBL1 can interact and sponge miR-1, a key cardiomyocyte differentiation promoter, to impair cardiomyocyte differentiation (Lu T.Y. et al, 2013;Liu et al, 2017). LncRNA Braveheart (Bvht) is exclusively expressed in the heart and can promote cardiovascular lineage commitment of mESCs by activating functional upstream genes of the MesP1, a permissive regulator of multipotent cardiovascular progenitor (Bondue et al, 2008(Bondue et al, , 2011.…”
Section: Lncrna In Cardiovascular Developmentmentioning
confidence: 99%